145k views
1 vote
If f(x) = 6x2 - 4 and g(x) = 2x+ 2, find (f - g)(x).

O A. 6x2 - 2x - 6
O B. 6x2 - 2x-2
O c. 44²-6
O D. 2x - 5x2 - 2

2 Answers

4 votes

Answer:

A. 6x^2 - 2x - 6.

Explanation:

( f - g)(x)

= 6x^2 - 4 - (2x + 2)

= 6x^2 - 4 - 2x - 2

= 6x^2 - 2x - 6.

User Catskul
by
5.5k points
0 votes

Answer:

A

Explanation:

Note that (f - g)(x) = f(x) - g(x)

f(x) - g(x)

= 6x² - 4 - (2x + 2) ← distribute parenthesis by - 1

= 6x² - 4 - 2x - 2 ← collect like terms

= 6x² - 2x - 6 → A

User Wisbucky
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.